Segments: An alternative rainfall problem. (19th October 2021) - ACHTEN, PETER
Abstract: Elliot Soloway's Rainfall problem is a well-known and well-studied problem to investigate the problem-solving strategies of programmers. Kathi Fisler investigated this programming challenge from the point of view of functional programmers. She showed that this particular challenge gives rise to five different high-level solution strategies, of which three are predominant and cover over 80% of all chosen solutions. In this study, we put forward the Segments problem as an alternative challenge to investigate the problem-solving skills of functional programmers. Analysis of the student solutions, their high-level solution strategies, and corresponding archetype solutions shows that the Segments problem gives rise to seven different high-level solution strategies that can be further divided into 17 subclasses. The Segments problem is particularly suited to investigate problem-solving skills that involve list processing and higher-order functions.